Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea) - Ng, Peter K.l.; Kumar, Appukuttannair Biju (Zootaxa, 2016)
A new species of Carcinoplax H. Milne Edwards, 1852 (family Goneplacidae) is described from southern India. Carcinoplax fasciata n. sp. is closest to C. specularis Rathbun, 1914, but can be distinguished by its different coloration in life as well as structures of the carapace surface, anterolateral armature, supraorbital margin, chela and male first gonopod.